2021
DOI: 10.29313/gmhc.v9i1.6227
|View full text |Cite
|
Sign up to set email alerts
|

Effectiviness of Lime Peel Extract (<i>Citrus aurantifolia</i> Swingle) against C-Reactive Protein Levels in Alloxan-Induced Wistar Rats

Abstract: Hyperglycemia is a metabolic disease that is most often found and continuously increasing. Various complications due to hyperglycemia in the blood can cause tissue damage. It will increase free radicals that can trigger an inflammatory response characterized by an increased C-reactive protein in the blood. Prevention can be done by administering flavonoid antioxidant and lime peel containing high flavonoid. This study aims to analyze the efficacy of lime peel extract against C-reactive protein level with hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(20 reference statements)
1
2
0
Order By: Relevance
“…In this study, the serum level CRP was significantly high in the inflammation control group (1.70±0.07ng/ml) when compared with 7 days (1.05±0.06ng/ml) and 14 days (0.93±0.05ng/ml) Bio-Clean II treated rats, as well as the zero control rats (0.92±0.03ng/ml). The outcome of this study is consistent with the work of Suryadinata et al, who evaluated the effect of 30 days treatment with lime peel extracts (Citrus aurantifolia swingle) against C-reactive protein levels in Alloxan-induced wistar rats [40]. In their study, CRP value was reported to be high in the alloxan induced rats (>12mg/ mL) when compared to the non-induced rats (<6mg/mL) and lime peel extract treated rats (<12mg/mL).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the serum level CRP was significantly high in the inflammation control group (1.70±0.07ng/ml) when compared with 7 days (1.05±0.06ng/ml) and 14 days (0.93±0.05ng/ml) Bio-Clean II treated rats, as well as the zero control rats (0.92±0.03ng/ml). The outcome of this study is consistent with the work of Suryadinata et al, who evaluated the effect of 30 days treatment with lime peel extracts (Citrus aurantifolia swingle) against C-reactive protein levels in Alloxan-induced wistar rats [40]. In their study, CRP value was reported to be high in the alloxan induced rats (>12mg/ mL) when compared to the non-induced rats (<6mg/mL) and lime peel extract treated rats (<12mg/mL).…”
Section: Discussionsupporting
confidence: 90%
“…italica) contains various types of non-enzymatic antioxidants and high polyphenol, including flavonoids, which is estimated to reduce free radicals and inflammation caused by cigarette smoke exposure. 33,34 This vegetable also contains selenium, and is known to potentially increase various enzymatic antioxidants, including superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px). 35…”
Section: Articlementioning
confidence: 99%
“…Which are obtained not only from its main part (the pulp) but also its peel. (18) Therefore, this study aimed further understand the effect of antioxidant in lime peel to decrease free radicals induced by hyperglycemia. In initial form, this study used experimental animals, i.e.…”
Section: Introductionmentioning
confidence: 99%